The Influence Mechanism of Purchase Intention of Domestic Brand Apparel for Middle-aged and Elderly People from the Consumption View - Pengbo Qian, Beijia Zhang, Yuchen Ding, Keyan Xu, Qingju Liu (Forest Chemicals Review, 2022)
This paper explores the mechanism influencing middle-aged and elderly people's willingness to purchase domestic brand apparel from the perspective of consumption. The authors use the structural equation modeling method, and analyze from the level of rational consumption and perceptual consumption. The results show that at the rational consumption level, product perceptions promote and hinder middle-aged and elderly consumers' willingness to purchase domestic brands by positively influencing perceived value and negatively influencing perceived risk, respectively. At the level of perceptual consumption, the degree of identity integration can contribute to the willingness of middle-aged and elderly consumers to purchase domestic brands by negatively influencing psychological distance and positively influencing perceived competence. In addition, although the degree of identity integration can positively affect warmth perception, there is no correlation between warmth perception and purchase intention. Finally, the total effect of rational consumption path on purchase intention is much larger than that of perceptual consumption path.